Limited Sampling Modeling for Estimation of Phenotypic Metrics for CYP Enzymes and the ABCB1 Transporter Using a Cocktail Approach - Coelho, Eduardo Barbosa; Cusinato, Diego Alberto Ciscato; Ximenez, João Paulo; Lanchote, Vera Lucia; Struchiner, Claudio José; Suarez-Kurtz, Guilherme (Frontiers in Pharmacology, 2020)
Plasma concentration data points (n = 2,640) from 16 healthy adults were used to develop and validate limited sampling strategies (LSS) for estimation of phenotypic metrics for CYP enzymes and the ABCB1 transporter, using a cocktail of subtherapeutic doses of the selective probes caffeine (CYP1A2), metoprolol (CYP2D6), midazolam (CYP3A), losartan (CYP2C9), omeprazole (CYP2C19) and fexofenadine (ABCB1). All subsets linear regression modelling was applied to estimate the AUC0-12h for caffeine, fexofenadine and midazolam, and the AUC0-12h ratio of metoprolol:-OH metoprolol and omeprazole:5-OH omeprazole. LSS-derived metrics were compared with the parameters´ 'best estimates' obtained by non-compartmental analysis using all plasma concentration data points. The correlation coefficient (R2) was used to identify the LSS equations that provided the best fit for n timed plasma samples, and the jack-knife statistics was used as an additional validation procedure for the LSS models. Single time-point LSS models provided R2 values greater than 0.95 (R2 > 0.95) for the AUC0-12h ratio of metoprolol:-OH metoprolol and omeprazole:5-OH omeprazole, whereas 2 time-point models were required for R2 > 0.95 for the AUC0-12h of caffeine, fexofenadine and midazolam. Increasing the number of sampling points to three led to minor increases in R2 and/or the bias or prediction of the estimates. In conclusion, the LSS models provided accurate prediction of phenotypic indices for CYP1A2, CYP2C19, CYP2D6, CYP3A and ABCB1, when using subtherapeutic doses of selective probes for these enzymes and transporter.